THE ENGLISH PREPOSITIONAL PHRASES USING PREPOSITIONS BY, WITH, AND WITHOUT WITH THEIR INDONESIAN TRANSLATION EQUIVALENTS IN REFERENCE TO “BHAGAVAD-GITA AS IT IS” AND ITS INDONESIAN TRANSLATION “BHAGAVAD-GITA MENURUT ASLINYA” - I Wayan Suardhana (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
This present study entitled The English Prepositional Phrases Using Prepositions By, With, and Without with Their Indonesian Translation Equivalents in Reference to “Bhagavad-Gita As It Is” and Its Indonesian Translation “Bhagavad-Gita Menurut Aslinya” was intended to identify (1) what types of lexical and syntactical forms of the English prepositional phrases using By, With, and Without were found in the data source “Bhagavad-Gita As It Is”; (2) what shifts occurring in the process of translating the English prepositional phrases using By, With, and Without into Indonesian; and (3) what were the Indonesian closest equivalents of the English prepositional phrases using By, With, and Without. The qualitative method was used in the study and the data were obtained through library research using observation and note-taking techniques. The data were taken from the Vedic scripture “Bhagavad-Gita As It Is” by A.C. Bhaktivedanta Swami Phrabupada and its Indonesian translation “Bhagavad-Gita Menurut Aslinya”. The data were descriptively analyzed using the theory of translation procedures proposed by Vinay and Dalbernet (2000), the theory of loss, gain, and skewing of information proposed by Nida (1975), and the theory of shift proposed by Catford (2000). The result shows that (1) there were a great number of prepositional phrases using By, With, and Without; (2) the shifts occurred from one word class to another word class and from one unit to another unit, (3) the procedures applied by the translator were word per word translation, borrowing, transposition, and modulation, and (4) the Indonesian translation equivalent of the preposition “by” is “oleh”, the Indonesian translation equivalent of the preposition of “with” is “dengan”, and the Indonesian translation equivalent of “without” is “tanpa”.